Penerapan Metode Extreme Programming Pada Sistem Informasi Pengendalian Bahan Baku Produksi - Ahlan Ismono; Denny Riandhita AP (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
Manufacturing companies, especially those engaged in the food processing machinery industry, often have problems. The raw material inventory control system in data processing is still not optimal due to the use of paper. Design and build a raw material inventory control system that is very necessary in the company to carry out the process of controlling raw material inventory. This computerized raw material control system proposes to make it easier to record data for admin and warehouse officers in supervising the recording and releasing of raw materials from the warehouse. The development of this production reporting information system uses the Extreme Programming (XP) method. System modeling using unified modeling language (UML), data modeling using entity relationship diagrams (ERD), and system design using windows navigation diagrams (WND) and interface design. Making this raw material inventory control system application using PHP with CodeIgniter and MariaDB frameworks. This Raw Material Inventory Control System is expected to make it easier for companies to record raw material data more precisely, quickly, and well supervised and can anticipate the occurrence of human errors in the PPIC division, especially for the warehouse section.